The implementation of e-government for village good governance in South Misool, Raja Ampat - Yoga Andriyan; M. Munzir; Andi Sismar; Wa Ode Likewati; Aldila Mawanti Athirah; Rahmat Hidayat; H. Henraman; Dhimas Ari Bhima Sakti (Universitas Muhammadiyah Malang, 2024)
This community service aims to implement E-Government as a solution to improve village governance in South Misool, Raja Ampat. Villages in the region often face challenges in managing public administration effectively and transparently, especially in the context of remote islands. The methodology of this service is Preparation, Interview, Socialization, Evaluation, and Reporting. Socialization in this service uses the method of lectures, discussions and sharing sessions. Socialization to improve knowledge and skills about e-government and efficient and effective village governance in South Misool, Raja Ampat. In South Misool, Raja Ampat, the implementation of E-Government reduces bureaucracy and increases the accountability of village governments. In addition, E-Government can help improve the quality of village apparatus human resources through mentoring and technology training, so that they are better prepared to face modern challenges. The results of this service are increasing knowledge of E-Government Implementation for Village Government Governance in South Misool, Raja Ampat (80%), Increasing human resource skills in using E-Government (70%), Increasing knowledge related to e-government-based governance (90%), Increasing knowledge related to public services (90%). It is very necessary to carry out similar activities by carrying out the village government needs to improve technological infrastructure, including adequate internet access and the necessary hardware, to support the implementation of E-Government in the Village Government in South Misool.